Digital mental health literacy -program for the first-year medical students’ wellbeing: a one group quasi-experimental study - Marjo Kurki (BMC, 2021)
Abstract Background Medical students are prone to mental disorders, such as depression and anxiety, and their psychological burden is mainly related to their highly demanding studies. Interventions are needed to improve medical students’ mental health literacy (MHL) and wellbeing. This study assessed the digital Transitions, a MHL program for medical students that covered blended life skills and mindfulness activities. Methodology This was a one group, quasi-experimental pretest-posttest study. The study population was 374 first-year students who started attending the medical faculty at the University of Turku, Finland, in 2018-2019. Transitions was provided as an elective course and 220 students chose to attend and 182 agreed to participate in our research. Transitions included two 60-minute lectures, four weeks apart, with online self-learning material in between. The content focused on life and academic skills, stress management, positive mental health, mental health problems and disorders. It included mindfulness audiotapes. Mental health knowledge, stigma and help-seeking questionnaires were used to measure MHL. The Perceived Stress Scale and General Health Questionnaire measured the students’ stress and health, respectively. A single group design, with repeated measurements of analysis of variance, was used to analyze the differences in the mean outcome scores for the 158 students who completed all three stages: the pre-test (before the first lecture), the post-test (after the second lecture) and the two-month follow-up evaluation. Results The students’ mean scores for mental health knowledge improved (-1.6, 95% Cl -1.9 to -1.3, P<.001) and their emotional symptoms were alleviated immediately after the program (0.5, 95% Cl 0.0 to 1.1, P=.040). The changes were maintained at the two-month follow up (-1.7, 95% Cl -2.0 to -1.4, P<.001 and 1.0, 95% Cl 0.2 to 1.8, P=.019, respectively). The students’ stress levels reduced (P=.022) and their attitudes towards help-seeking improved after the program (P<.001), but these changes were not maintained at the two-month follow up. The stigma of mental illness did not change during the study (P=.13). Conclusions The digital Transitions program was easily integrated into the university curriculum and it improved the students’ mental health literacy and wellbeing. The program may respond to the increasing global need for universal digital services, especially during the lockdowns due to the COVID-19 pandemic. Trial registration The trial was registered at the ISRCTN registry (26 May 2021), registration number 10.1186/ ISRCTN10565335 ).